الموازنة بين المصالح والمفاسد في ضوء قصة موسى مع الخضر في سورة الكهف - قطران، أحمد بن صالح محمد (جامعة القرآن الكريم والعلوم الإسلامية, 2022)
الابتلاء الذي تعرض له موسى عليه السلام مثلا منهجيا للموازنة بين المصالح والمفاسد، وعليه يمكن صياغة مشكلة البحث في السؤال الآتي: ما هي صور الموازنة بين المصالح والمفاسد في قصة موسى مع الخضر عليهما السلام؟ وتفرع عنه عدد من الأسئلة الفرعية أجاب عنها البحث في ثناياه، وهدف البحث إلى بيان مدى تطبيق الموازنة بين المصالح والمفاسد في القصة، والاستفادة منها في الواقع، وحتى يسير البحث وفق منهجية دقيقة فقد تم اختيار المنهج الوصفي، والمنهج الاستقرائي، وتوصل البحث إلى عدد من النتائج أهمها: 1. إن العناء والمصاعب التي لقيها موسى عليه السلام في هذه الرحلة الشاقة تدل بما لا يدع مجالا للشك أن طلب العلم تهون معه كل المشاق. 2. نستنتج من القصة وجوب السفر والهجرة لطلب العلم إذا لم يجد ما يحتاجه في البلد التي يقيم بها من العلوم التي تخدم الأمة. 3. إن الموازنة في هذه القصة تختلف باختلاف شخصها فموسى عليه السلام موازناته تعتمد على الصورة الظاهرة، بينما موازنة الخضر عليه السلام تعتمد الصورتين الظاهرة والباطنة. The test that Moses, peace be upon him, was subjected to was a method of balancing benefits and evils, and accordingly the research problem can be formulated in the following question: What are the forms of reconciliation between interests and evils in the story of Moses with al-Khidr, peace be upon them? A number of sub-questions branched out from it, which were answered by the research, and the aim of the research is to demonstrate the extent to which the balance between interests and corruption is applied in the story, and to benefit from it. In fact, in order for the research to proceed according to a precise methodology, the descriptive method and the inductive method were chosen. The most important results: 1- The hardships and hardships that Moses, peace be upon him, went through on this arduous journey indicate beyond any doubt that seeking knowledge relieves all hardships. 2- We conclude from the story that it is obligatory to travel and migrate in order to seek knowledge if he does not find what he needs in the country in which he resides of sciences that serve the nation. 3- The balance in this story varies according to its person, for Moses, peace and blessings of God be upon him, his scales depend on the outward image, while the scales of al-Khidr, peace be upon him, depend on the outward and inward.
Keywords: قصص الأنبياء -- الفقه الإسلامي -- رسائل الهداية -- المنافع الشرعية